Effect of ricinoleic acid esters from castor oil (Ricinus communis) on the oocyte yolk components of the tick Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) - Sampieri, Bruno Rodrigues [UNESP]; Arnosti, André [UNESP]; Furquim, Karim Christina Scopinho [UNESP]; Chierice, Gilberto Orivaldo [UNESP]; Bechara, Gervásio Henrique [UNESP]; de Carvalho, Pedro Luiz Pucci Figueiredo [UNESP]; Nunes, Pablo Henrique [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Elsevier, 2013)
Rhipicephalus sanguineus are bloodsucking ectoparasites, whose main host is the domestic dog, thus being present in urban areas and closely located to people. Eventually, this tick species parasitize humans and can become a potential vector of infectious diseases. Methods to control this type of pest have been the focus of many research groups worldwide. The use of natural products is increasingly considered nowadays, due to the low toxicity levels to the host and low waste generation to the environment. This study tested the effect of ricinoleic acid esters from castor oil (as an potential acaricide) on the reproductive system of R sanguineus females, more specifically on the vitellogenesis process. For this, two groups were established: the control group (CG) and the treatment group (TG) with five rabbits in each (New Zealand White), used as hosts. NaCl and ester were added to rabbits' food and offered to the hosts. After full engorgement, the females were collected and had their ovaries extracted. The ticks ovaries were submitted to histochemical techniques so the effects of esters could be observed over polysaccharides, proteins and lipids yolk. Changes in the deposition of yolk components were observed. This caused modifications on elements of polysaccharide origin and on glycoprotein compounds, interfering in the final yolk synthesis and compromising the development of the future embryo. © 2012.
Keywords: Castor oil; Control; Esters; Rhipicephalus sanguineus; Ricinus communis; Vitellogenesis; acaricide; castor oil; glycoprotein; lipid; polysaccharide; ricinoleic acid; sodium chloride; yolk protein; animal cell; animal experiment; animal food; animal tissue; controlled study; egg yolk; embryo development; female; histochemistry; nonhuman; oocyte; ovariectomy; rabbit; reproduction; Rhipicephalus; vitellogenesis; Animals; Antiparasitic Agents; Castor Oil; Female; Oocytes; Acari; Canis familiaris; Ixodida; Ixodidae; Oryctolagus cuniculus